DAMPAK PELATIHAN KERJA DALAM MENINGKATKAN KOMPETENSI PENCARI KERJA OLEH DINAS TENAGA KERJA DAN PERINDUSTRIAN KOTA PADANG - Marshanda, Serli; Westika Putri, Sinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The job training conducted by the Padang City Manpower and Industry Office aims to improve the competence of job seekers. However, how the impact of job training on job training participants still needs to be studied further. This study aims to see the impact of job training in improving the competence of job seekers by the Padang City Manpower and Industry Office. The research uses qualitative research methods with data collection techniques through interviews and documentation. This research involved informants consisting of the Padang City Manpower and Industry Office, LPK who cooperated, participants, job seekers who have not participated in the training and agencies that accept training participants through purposive sampling techniques. Data is analyzed through the stages of data collection, data reduction, data presentation and conclusion drawn. The results showed that job training participants gained improved knowledge and skills and attitudes. This shows that there is an increase in competence in the training participants. Then, some of the trainees also got jobs or opened businesses after participating in the training. However, there is still a need to improve material on character development, post-training evaluation, and increase the duration of training. This study concludes that job training has a positive impact on improving the competence of job seekers, although there is a need for improvement in certain aspects.